2007
DOI: 10.1371/journal.pone.0000191
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Drops and the Onset of Severe Avian Influenza A H5N1 Virus Outbreaks

Abstract: Global influenza surveillance is one of the most effective strategies for containing outbreaks and preparing for a possible pandemic influenza. Since the end of 2003, highly pathogenic avian influenza viruses (HPAI) H5N1 have caused many outbreaks in poultries and wild birds from East Asia and have spread to at least 48 countries. For such a fast and wide-spreading virulent pathogen, prediction based on changes of micro- and macro-environment has rarely been evaluated. In this study, we are developing a new cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 7 publications
3
41
0
Order By: Relevance
“…Liu et al (2007) showed that a temperature drop occurred shortly before H5N1 outbreaks in birds in each of the Eurasian regions stricken in 2005 and 2006. The adverse freezing conditions around the Black Sea in the winter of 2006, forced mute swans (Cygnus olor) and other birds, to disperse to other areas, widening the outbreak area (GauthierClerc, Lebarbenchon, and Thomas 2007;Alexander 2007).…”
Section: Avian Communitymentioning
confidence: 99%
“…Liu et al (2007) showed that a temperature drop occurred shortly before H5N1 outbreaks in birds in each of the Eurasian regions stricken in 2005 and 2006. The adverse freezing conditions around the Black Sea in the winter of 2006, forced mute swans (Cygnus olor) and other birds, to disperse to other areas, widening the outbreak area (GauthierClerc, Lebarbenchon, and Thomas 2007;Alexander 2007).…”
Section: Avian Communitymentioning
confidence: 99%
“…The success of the virus to transmit in low temperatures is also likely to arise from the effect of cold weather on the host and associated suppression of the immune system. Analysis of HPAI H5N1 activity during 2005 -2006 indicated that 27 outbreaks were preceded by a drop in temperature due to Siberian cold air mass dominating Eurasia (Liu et al, 2007;Ottaviani et al, in revision). Liu et al (2007) proposed that this dramatic weather fluctuation may have stressed birds already physically depleted from performing migration, making them susceptible to HPAI H5N1 infection.…”
Section: Immune Status and Conditionmentioning
confidence: 99%
“…Analysis of HPAI H5N1 activity during 2005 -2006 indicated that 27 outbreaks were preceded by a drop in temperature due to Siberian cold air mass dominating Eurasia (Liu et al, 2007;Ottaviani et al, in revision). Liu et al (2007) proposed that this dramatic weather fluctuation may have stressed birds already physically depleted from performing migration, making them susceptible to HPAI H5N1 infection. Furthermore, this drop in temperature may have resulted in crowding of wild birds into remaining unfrozen habitat, further contributing to stress and also facilitating density dependent virus transmission (Ottaviani et al, in revision).…”
Section: Immune Status and Conditionmentioning
confidence: 99%
“…Liu et al (2007) found that outbreaks of HPAI H5N1 in Eurasia occurred during or immediately after a rapid decrease in temperature. Temperature, NDVI (normalised difference vegetation index, a measure of vegetation greenness) and precipitation were found to be key environmental factors for creating accurate risk maps for H5N1 outbreaks in Europe (Gilbert and Pfeiffer 2012).…”
Section: Interactions Between Environmental Factors and Aiv Prevalencementioning
confidence: 99%